Readiness of student teacher in Nakorn Pathom Rajabhat University toward an ASEAN Community of Mutual Recongnition Arrangment. - Khamphon, Jantima; Klaychanphong, Hansa; Sanglertuthai, Jittirat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purposes of this research were to : 1) identify the readiness level of the NPRU ,s student teacher in mutual recognition arrangement to meet the AEC ; 2) compare students, readiness level as classified by gender, faculty of study, field of study , and the GPA : 3) compile the students, opinion toward readiness preparation. Sample was 302 the NPRU student teachers in academia year 2015 derived by stratified random sampling distributed by the field of study. Data were analyze with percentage, mean , standard deviation, t-test, One – way ANOVA and 10 key informants such as president and supervisor are derived by purposive sampling – Instruments used to collect data were questionnaire. Constructed interview form designed by the researcher. The results found that : 1) The student teachers, level of readiness to meet the AEC were at the high level in all aspects, respectively from the highest in Knowledge, ASEAN’ s teaching professional information, Attitude and English communication skills. 2) student teachers, readiness preparation were different with statistical significance at 0.05 as classified by field of study, however, there were no statistical different as classified by gender, faculty of study and the GPA 3) The compiled opinions toward the student teachers, preparation to meet the AEC were (1) Knowledge : that knowledge ability of basic information concerning ASEAN countries and the applicability for teaching and learning management in the field while performing student teaching practicum ; (2) English communication skill, that English medium as well as individual’s native language were needed for practical communication ; (3) The ASEAN ,s skills in teaching professional information, that the ability to learn from internet information, documentary, principles and ideas from the key educations were needed to meet the teaching profession’s advancement ; (4) Attitude , that the openness in acceptance of other cultures that were different from one, own, exchanging of knowledge as well as ability to access new information, technology and innovation, ability to think and analyze the newly gained information, thoughtfully, and adaptability to cultural differences among the ASEAN countries effectively. Article history : Accepted 28 April 2016 SIMILARITY INDEX = 0.00